OA01.41. Selective ayurvedic therapy for the management of major depressive disorder: A randomised control trial - Fulzele, Ashwini (Medknow Publications & Media Pvt Ltd, 2012)
PURPOSE: Mental health is the level of psychological well being and encompasses the abilities to develop emotionally, psychologically, intellectually, socially and spiritually. There is no health without mental health. Most common mental disorder is depression, anxiety & drug addiction. Major depressive disorder is a mental disorder characterised by an all encompassing low mood accompanied by low self esteem and loss of interest in normally enjoyable activities. Standard treatment for depression includes antidepressant medication which have unpleasant side effect and psychotherapy which is time consuming and expensive. Objective of the present study was to assess the effectiveness of a herbal preparation and shirodhara therapy for the treatment of major depressive disorder and to compare its effectiveness with a standard drug. METHOD: It was Open Randomised Controlled clinical Study. Study population was selected from OPD & IPD of Kaychikitsa department at NIA and OPD of Psychiatry, SMS Medical College & Hospital, Jaipur. Out of 42 screened patients, 30 patients fulfilling the DSM-IV criteria for diagnosis of depression were enrolled for the study and randomly divided into two groups. Group A was given standard drug fluoxetine 20mg orally BD for 42 days. Group B was given herbal preparation orally for 42 days with shirodhara by medicated plain Ashwagandha oil for 14 days. Observations were made on baseline day, 14thday, and 28thday and 42nd day of study. RESULT: Both the groups showed significant improvement, with no unpleasant side effect in Group B. CONCLUSION: Selected Herbal preparation and Shirodhara therapy can be used in mild & moderate condition of major depression with free of side effect.